Potencjalne możliwości wykorzystania biomasy drzewnej do celów energetycznych - Parzych, Stanisław (Leśne Prace Badawcze, 2015)
This paper presents results of a meta-analysis on the theoretical and economic aspects of using wood biomass for the production of energy in Poland. The source data used in the analyses were obtained from various official sources and statistics as well as previously published scientific studies. The results lead to the conclusion that the wood biomass supplied for energy production in the year 2012 amounted to a total of 18 million cubic meters, of which forestry supplied 6.8 million m 3 , the wood industry 6.5 million m 3 and public utilities provided 4.5 million m 3 .